+0  
 
+5
231
2
avatar

3a divided by 5 - 6 = 3

Guest Feb 25, 2017
 #1
avatar+7155 
+2

\(\frac{3a}{5-6} = 3 \\ \frac{(5-6)3a}{5-6}=3(5-6) \\ 3a=3(-1) \\ a=-1\)

 

If you meant - 6 not in the denominator it's:

 

\(\frac{3a}{5}-6 = 3 \\ \frac{3a}{5}-6+6 = 3 + 6 \\ \frac{3a}{5} = 9 \\ \frac{(5)3a}{5} = (5)9 \\ 3a=45 \\ 3a/3=45/3 \\ a=15\)

hectictar  Feb 25, 2017
 #2
avatar+7002 
0

\(\dfrac{3a}{5}-6 = 3\\ \dfrac{3a}{5}=9\\ \dfrac{a}{5}=3\\ a=15\)

MaxWong  Feb 25, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.